C-Methionine Positron Emission Tomographic Imaging of Biologic Activity of a Recurrent Glioblastoma Treated with Stereotaxy-Guided Laser-Induced Interstitial Thermotherapy - Norbert Galldiks; Wernholt von Tempelhoff; Deniz Kahraman; Lutz W. Kracht; Stefan Vollmar; Gereon R. Fink; Michael Schroeter; Roland Goldbrunner; Matthias Schmidt; Mohammad Maarouf (Molecular Imaging)
In patients with recurrent glioblastoma multiforme (GBM), local minimally invasive treatment modalities have gained increasing interest recently because they are associated with fewer side effects than open surgery. For example, local tumor coagulation by laser-induced interstitial thermotherapy (LITT) is such a minimally invasive technique. We monitored the metabolic effects of stereotaxy-guided LITT in a patient with a recurrent GBM using amino acid positron emission tomography (PET). Serial 11 C-methyl-L-methionine positron emission tomography (MET-PET) and contrast-enhanced computed tomography (CT) were performed using a hybrid PET/CT system in a patient with recurrent GBM before and after LITT. To monitor the biologic activity of the effects of stereotaxy-guided LITT, a threshold-based volume of interest analysis of the metabolically active tumor volume (MET uptake index of ≥ 1.3) was performed. A continuous decline in metabolically active tumor volume after LITT could be observed. MET-PET seems to be useful for monitoring the short-term therapeutic effects of LITT, especially when patients have been pretreated with a multistep therapeutic regimen. MET-PET seems to be an appropriate tool to monitor and guide experimental LITT regimens and should be studied in a larger patient group to confirm its clinical value.